2010
DOI: 10.1111/j.1526-4637.2010.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hepatotoxicity-Related Hospitalizations among Patients Treated with Opioid/Acetaminophen Combination Prescription Pain Medications

Abstract: There is no population data-based evidence supporting elevated risk of hepatotoxicity-related hospitalization associated with opioid/acetaminophen combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Epidemiologic studies of hospitalisation for ALI are limited: A case‐crossover study by Lee et al demonstrated that nimesulide, diclofenac, ibuprofen, and other NSAIDs are associated with an increased risk of hospitalisation for acute hepatitis . On the other hand, the pre‐post study by Duh et al, aiming to determine the risk of serious hepatotoxicity resulting in hospitalizations among patients prescribed opioid/acetaminophen combinations, could not find an association between hepatotoxicity‐related hospitalisation and opioid‐paracetamol combination medications …”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies of hospitalisation for ALI are limited: A case‐crossover study by Lee et al demonstrated that nimesulide, diclofenac, ibuprofen, and other NSAIDs are associated with an increased risk of hospitalisation for acute hepatitis . On the other hand, the pre‐post study by Duh et al, aiming to determine the risk of serious hepatotoxicity resulting in hospitalizations among patients prescribed opioid/acetaminophen combinations, could not find an association between hepatotoxicity‐related hospitalisation and opioid‐paracetamol combination medications …”
Section: Discussionmentioning
confidence: 99%
“…Eliminating opioid/acetaminophen combination products will have a very significant impact on pain management. In one analysis of claims data for hydrocodone or short‐acting oxycodone pain medications, one in six claimants received an opioid/acetaminophen combination medication at some time over an 8‐year period [21]. The actual consequences on patient care of removing the most commonly prescribed pain medications for patients with moderate to moderately‐severe pain are unknown.…”
Section: Consequences Of Following Advisory Committee's Recommendationmentioning
confidence: 99%
“…significant number of unintentional overdose cases which often lead to acute liver failure and death [6][7][8][9][10][11]. As a result, the potential of APAP toxicity has created a dosage ceiling for those hydrocodone combination analgesics [10].…”
mentioning
confidence: 99%